2017
DOI: 10.4103/jips.jips_144_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of joining the sectioned implant-supported prosthesis on the peri-implant strain generated in simulated mandibular model

Abstract: Aim:The aim of this study is to evaluate the strain developed in simulated mandibular model before and after the joining of an implant-supported screw-retained prosthesis by different joining techniques, namely, arc welding, laser welding, and soldering.Materials and Methods:A specimen simulating a mandibular edentulous ridge was fabricated in heat-cured acrylic resin. 4-mm holes were drilled in the following tooth positions; 36, 33, 43, 46. Implant analogs were placed in the holes. University of California, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This study revealed that sectioning and reuniting the long-span implant prosthesis was found to be a significant factor in influencing the peri-implant strain, irrespective of joining methods such as arc welding, laser welding, and soldering. [ 18 ] When we see the literature on the digital impression for such cases, Gherlone EF used digital impressions in “All-on-Four” implant restorations. A digital scan body can be an adjuvant to get a definitive prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that sectioning and reuniting the long-span implant prosthesis was found to be a significant factor in influencing the peri-implant strain, irrespective of joining methods such as arc welding, laser welding, and soldering. [ 18 ] When we see the literature on the digital impression for such cases, Gherlone EF used digital impressions in “All-on-Four” implant restorations. A digital scan body can be an adjuvant to get a definitive prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The stresses generated in the bone surrounding implant prosthesis also depend on the implant design, material, structure, and dimensions. 33 The implant diameter is reported to be more important than implant length in distributing stresses to the surrounding bone. In a study conducted by Eazhil et al, 34 it was concluded that there was a statistically significant decrease in von Mises stress as the implant diameter increased.…”
Section: Wjdmentioning
confidence: 99%